(untitled) (Research, Society and Development, 2023)
In view of the scenario of human disturbances and regional climate change, we intend to verify whether habitats that are structurally more heterogeneous, complex and of higher quality, such as riparian forests, support a higher biodiversity of ant genera and their respective functional groups, when compared to more homogeneous environments and of low habitat quality such as abandoned pasture areas, as well as the effects of seasonality. A total of 4,865 ants belonging to 7 subfamilies and 15 ant genera were collected. The subfamilies that showed the highest representativeness (abundance) were Myrmicinae (4,436), followed by Formicinae (282), Ectatomminae (97), Dolichoderinae (18), Pseudomyrmecinae (15), Dorylinae (9) and Ponerinae (8). The high-quality habitat, which corresponds to riparian forest, had the highest richness of genera, characterized by the genus Nylanderia, with a higher occurrence of the functional group Generalist Myrmecinae, with high values of relative humidity in both seasons. On the other hand, the low-quality habitat showed less richness of genera, being the genus that caracterizes this environment the Crematogaster, with higher occurrence of the functional group of Tropical Climate Specialists and low values of relative humidity. In view of the above, this study provides subsidies for conservation work in riparian forest areas in the humid tropical forest biome. Besides warning about the reduction in the richness of ant genera due to the conversion of natural areas into pasture.